Regulation of Trust Management of Property - Topildiev Bakhromjon Rakhimjonovich (International Journal of Scientific Trends, 2024)
A Property Trust Management Agreement is a legally binding document that outlines the terms and conditions governing the relationship between a property owner (trustor) and a designated trustee responsible for managing and overseeing the trust property. This agreement typically covers various aspects, including property maintenance, leasing, financial management, and the distribution of income or proceeds. It serves as a crucial tool in establishing clear guidelines and responsibilities to ensure the effective and transparent management of trust assets.